Analysis of The Effect of Total Quality Management (TQM) Implementation on MSME Business Performance During The COVID 19 Pandemic (Study of Patin Processing Center XIII Koto Mesjid) - Setiawan, M. Hardi; Yahya, Mhd. Rafi; Syaputra, Widi (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
The era of globalization has intensified economic competition, compelling both large enterprises andMicro, Small, and Medium Enterprises (MSMEs) to innovate and adapt for survival and growth. This studyinvestigates the application of Total Quality Management (TQM) and its effects on business performance, witha focus on the patin fish farming community in Koto Mesjid village, Riau. The main issue discussed was thechallenge for MSMEs to maintain competitiveness amidst the pressures of global economic competition andthe COVID-19 pandemic, which has affected production processes and increased business competition. Aquantitative research approach was employed, involving a survey of 85 respondents from the entire population.Data were gathered through questionnaires, tested for validity and reliability, and analyzed using multiplelinear regression with SPSS version 25. The findings demonstrate that management leadership, customer focus,information and analysis, and continuous improvement positively and significantly influence MSME businessperformance. In contrast, the process management variable did not have a significant effect. This researchhighlights the crucial role of TQM in achieving competitive advantage and underscores the importance ofimproving identified weak areas to enhance overall business outcomes.Keywords: Total Quality Management, Business performance, Small and Medium Enterprises,